Educational and Family Factors in Child Autism: A Systematic Literature Review (Nigerian Journal of Physiological Sciences, 2025)
The early detection of autism spectrum disorders is considered the best strategy for managing, controlling, and intervening with the patients before they reach adulthood. There is a consensus among medical professionals and research communities about the mismatching criteria, confusing symptoms, and inexhaustive nature of symptoms. Also, there are no established diagnostic factors to date due to many more non-deterministic factors like gender, race, age and region. In this study, a systematic literature review (SLR) was done on educational and family factors affecting child autism spectrum disorder at early stages. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were adopted for selecting the forty-eight (48) items for the study. The results of this study revealed the educational and family factors for children with autism. This, in turn, will assist medical practitioners during the screening process, as well as help schools and specialised centres for autism plan effectively to meet the needs of integrated educational services for children with autism. This study also included a set of educational tools related to managing children with autism. This reveals some requirements in the field of assistive software, especially in the commencement of AI assistive tools for helping better and effective education in ASD kids. In addition to future research directions and areas of additional studies related to autism.